2019
DOI: 10.3390/app9183827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Uncertainty in Localized Imperfection on the Ultimate Compressive Strength of Cold-Formed Stainless Steel Hollow Sections

Abstract: Stainless steel has excellent corrosion resistance properties, considerable long-term durability, and good mechanical strength. Hollow sections are a versatile and efficient form for construction applications. The use of cold-formed stainless steel rectangular hollow section (RHS) and square hollow section (SHS) in construction industry grasps the attention of designers conceiving long-term, cost-effective structures. For cold-formed RHS and SHS, localized imperfection (ω) resulting from rolling and fabricatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…For each specimen type, at least three tests were carried out as recommended by the Australian Racking code (AS4084: 2012) [33]. The reason for the different ultimate values for these three tests of each specimen can be attributed to the fact that upright elements have different initial geometrical imperfections associated with the manufacturing processes [34].…”
Section: Resultsmentioning
confidence: 99%
“…For each specimen type, at least three tests were carried out as recommended by the Australian Racking code (AS4084: 2012) [33]. The reason for the different ultimate values for these three tests of each specimen can be attributed to the fact that upright elements have different initial geometrical imperfections associated with the manufacturing processes [34].…”
Section: Resultsmentioning
confidence: 99%
“…A B21 box section has 5 default Simpson integration points in the two walls of the section. Two iterative methods, the Newton method (load controlled) [24] and Arc-length method [25] are employed to compute the solution of nonlinear equilibrium equations. Based on preliminary mesh convergence study, the adopted mesh density is 100 elements per member.…”
Section: Numerical Modellingmentioning
confidence: 99%
“…1.). Localized imperfections, which are induced from rolling and fabrication process, have sufficient variability and have no definitive characterization [29]. Therefore, it is necessary to evaluate the sensitivity of the extended stiffness reduction factor (in conjunction with GNA) to random ω (both the shape and magnitude of ω varied randomly).…”
Section: Compression Elements Subject To Axial Compressionmentioning
confidence: 99%
“…In the current paper, the value of ω considered in the ρ factor is conservatively taken as the mean value of the maximum localized imperfection (ω max ) collected from reported tests. Statistical analysis of ω max of a total of 161 cold-formed stainless steel RHS and SHS members has already been provided in [29,36]. The study of Shen [36] showed that the mean value of ω max of the collected samples is 0.185.…”
Section: Calculation Of Nominal Buckling Strength and Momentmentioning
confidence: 99%